2020
DOI: 10.3390/ijerph17176434
|View full text |Cite
|
Sign up to set email alerts
|

Physical Performance, Anthropometrics and Functional Characteristics Influence the Intensity of Nonspecific Chronic Low Back Pain in Military Police Officers

Abstract: Background: Chronic low back pain (CLBP) is a serious problem in Military Police Officers (MPO), which accounts for up to 45% of the sick leave rates. It has been assumed that the strength and the endurance of trunk flexor and extensor muscles are CLPB key factors, but it is not known whether these attributes are related to pain intensity. It was aimed to determine whether the strength and endurance of trunk flexor and extensor muscles differ in MPO with no pain (CON; n = 24), moderate (MOD; n = 42), and sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Furthermore, certain positions require working abroad (e.g., embassies) or working away from their units for months due to reasons of national and public security, irrespective of the area they work (Scientific, Information, Immigration and borders, Judiciary and Public safety). Different studies carried out in Spain have shown that police officers are highly likely to suffer from work-related stress due to the tasks of their work [1], such as responding to emergency calls, arresting violators, delivering warrants, mediating conflicts between citizens promptly, which, in turn, harms their physical and psychological wellbeing [2][3][4]. Although previous research has also shown that flexibility-oriented cultures exert their positive effects on employees' job satisfaction (among others) [15], as far as our knowledge reaches, there is an absence of empirical studies focused on how a flexibility-oriented organizational culture can reduce the negative effects of work demands of Spanish police officers, that is to say, facilitate positive outcomes at the employee level.…”
Section: Study Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, certain positions require working abroad (e.g., embassies) or working away from their units for months due to reasons of national and public security, irrespective of the area they work (Scientific, Information, Immigration and borders, Judiciary and Public safety). Different studies carried out in Spain have shown that police officers are highly likely to suffer from work-related stress due to the tasks of their work [1], such as responding to emergency calls, arresting violators, delivering warrants, mediating conflicts between citizens promptly, which, in turn, harms their physical and psychological wellbeing [2][3][4]. Although previous research has also shown that flexibility-oriented cultures exert their positive effects on employees' job satisfaction (among others) [15], as far as our knowledge reaches, there is an absence of empirical studies focused on how a flexibility-oriented organizational culture can reduce the negative effects of work demands of Spanish police officers, that is to say, facilitate positive outcomes at the employee level.…”
Section: Study Aimsmentioning
confidence: 99%
“…Nowadays, police organizations face a wide range of environmental pressures and police officers should attempt to tailor their operations and services to the community's needs [1]. In order to perform their functions by maximizing the results of their efforts, police officers' physical and psychological wellbeing should be considered as a relevant topic [2][3][4], since empirical evidence has shown the link between personal wellbeing and positive outcomes, such as job satisfaction, organizational commitment, and citizenship behaviors [5,6]. Furthermore, any organizational effort to alter the work environment should be also reflected in the culture of the organization and be transmitted through organizational socialization.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there has been no reliable treatment for LBP. The investigation of risk factors and prevention strategies for LBP remains to be a research priority (12)(13)(14). Practically, pharmacological or interventional treatments may be subject to certain conditions and are associated with severe adverse effects, such as addiction and surgical complications.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing flexibility exercises before and during the patrol season would be beneficial to help police officers reduce the muscle tension caused by the high level of physical activity from bike patrolling. Considering that the lower back region is known to be weaker among the police population, it would be interesting to measure the strength and endurance of the lumbar region in specialized police officers, such as bike patrollers, to help determine whether the physical demand for the job presents health risks for the officers [39]. The riding position throughout the season could also be evaluated in future studies to assess whether the particular positioning of the officers on their bike exposes them to a higher prevalence of low back pain or other discomfort [40,41].…”
Section: Discussionmentioning
confidence: 99%